Resilient Co-Production Of Peripheral Popular Urbanisation In Buenos Aires Metropolitan Region: The Case Of Guernica Land Reappropriation - Ferlicca, Francesca (2025)
The social and economic emergency unleashed by the COVID-19 pandemic in Argentina had its correlate in a new housing crisis on a national scale. One of its main expressions was a new wave of informal land occupations in the metropolitan peripheries. In this scenario, a large land occupation known as Toma de Guernica took place in the southern area of the Buenos Aires Metropolitan Region. The aim of this chapter is to analyze the synergy between inhabitants, grassroots social organizations and academia, that led to the collective development of an urbanization project that supported the claim for the right to land and housing. This articulation is addressed in terms of a resilient co-production of urban planning and design strategies in terms of urban governance. Underlying conflicts like this is the need to return the use of land to the sphere of social needs, privileging its use value over its exchange value. In this sense, land occupations have recently been referred as "land reappropriations" endorsing the interests, housing needs, and perspectives of vulnerable groups and their organizations. We believe that Guernica Land Reappropriation is a laboratory of new counter-hegemonic practices, insurgent popular planning and direct democracy, where a new way of cooperation and synergistic co-production between the academy and the working classes emerged and contributed to foster the capacities of communitarian resilience in times of crisis.